Measuring the inter-structural low-carbon economic inequalities from perspectives of industrial heterogeneity and scale economy: A case study of China’s 29 non-ferrous metal industries - Sun, Lu-Xuan; Wang, Miao; Xia, Yin-Shuang; Feng, Chao (Technological and Economic Development of Economy, 2022)
With the rapid energy consumption increase in China’s non-ferrous metal industry (NMI), there are inequalities in energy-related CO2 emissions among the sub-sectors. In this paper, a meta-frontier decomposition analysis was proposed for decomposing inter-structural low-carbon economic development inequalities among 29 sub-sectors in China’s NMI from 2004 to 2018 into 11 components, including four new factors, i.e., energy- and output- oriented technological gaps and scale economies. In addition, an I(CI) index is constructed to measure the inter-inequalities of low-carbon economic development among NMI and decomposed from the static and dynamic perspectives, respectively. Results show that: (1) I(CI) index was in a downward trend during 2004–2010, while remained stable during 2010–2018; (2) the energy-oriented technological gap (ETG) was the key promoters to increase I(CI); (3) the potential energy intensity (PEI) was the primary inhibiting factor for I(CI); (4) the government can reduce the inter-inequalities by narrowing the technological gap and reducing potential energy intensity in the energy market. First published online 20 May 2022